Pengembangan Kompetensi Bahasa Inggris Guru di SD Muhammadiyah 5 Porong - Taufiq, Wahyu; Agustina, Sheila; Novita, Dian (Society : Jurnal Pengabdian Masyarakat, 2022)
Community service activities aimed at teachers in the Muhammadiyah 5 Porong Elementary School in the form of training and mentoring of English language materials are based on the need for the application of the use of English in the school environment, especially since English has become a local content lesson. This service activity is carried out for 6 months. In this activity, training and mentoring is(Permatasari, Ressa Dwi Citra; Taufiq, 2021) centered on three main materials, namely the use of English in the classroom, namely the use of English that can be inserted or included in the material taught by the teacher. The second material is English for activities outside the classroom, namely interaction activities between teachers and students outside of class hours and the third is English for daily communication, which can be practiced between teachers on various occasions within the school. The teachers are very enthusiastic about this activity, and it is hoped that there will be follow-up activities related to the material taught later. Furthermore, it is hoped that after this activity, teachers will be able and brave to teach in English, using it in school activities and in daily activities to support the use of English in schools.